Optimalisasi Passage Planning Pada Electronic Chart Display and Information System Guna Meningkatkan Keselamatan Pelayaran: Studi Kasus Psv Anggrek 601 - Sulthan Shalahuddin Anhar; Minto Basuki (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
Before carrying out sailing activities as a navigator on a ship, the thing you must prepare is, prepare everything related to the cruise plan. This aims to minimize the occurrence of accidents on ships when sailing. Making passage plans is usually made using paper maps, but this is a long and inefficient method to do. So, with current technological advances, several systems and tools have been created to make it easier to create passage plans, namely digital maps or better known as Electronic Charts. Electronic Chart Display and Information Systems (ECDIS) is a tool whose function and system can provide information about navigation and whose use is to back up existing equipment, so that it can be accepted and considered to meet the requirements determined by the 1974 SOLAS convention & its amendments. Electronic Chart Display and Information Systems (ECDIS) is an integration of various navigation tools, namely Global Positioning System (GPS), Radio Direction and Ranging (RADAR), Automatic Identification System (AIS), Echo Sounder and Gyro Compass. Starting from this awareness that there are many advantages in operating ECDIS on ships, we should realize that using ECDIS to make shipping plans (Passage Planning) can help lighten the burden on officers on board ships in designing a good and safe shipping route. The impact of making a passage plan that is inaccurate/not rechecked on the nautical chart that is generated as input to ECDIS and causes accidents when the ship is navigating.